Biological inspiration in architectural design: reviewing the influence of the living world on architectural theory and practice - Najafi, Elaheh; Faizi, Mohsen; Khanmohammadi, Mohammad Ali (Penerbit Universiti Kebangsaan Malaysia, 2020)
Analogy is a main cognitive source, which helps to understand new ideas and fosters creativity. Making analogy has a significant role in the architectural design thinking process and creating architectural concepts. The living nature has been always a great source of inspiration for the architects during history. Biological inspiration can be traced in various aspects of architectural theory and practice during the history. In the present research, different aspects of the influence of living nature and biology are investigated after an extensive literature review and classified in categories including as bio-utilization, inspiration in form, structure, mechanism, process, function, system, theory, abstract rule and concept. Accordingly, only some aspects of biological inspiration can be considered as biological analogies, including structure, mechanism, process, function, system, abstract rule and theory. Studying the history of bio-inspired architecture showed a gradual move from biological morphology, which was a superficial similarity, towards the deeper aspects of biological analogies in bionic design. It is because; bionic provides a deeper understanding of living nature. Besides, more efficient, optimized, and sustainable architecture could be achieved through the inspiration of deeper biological analogies in comparison to the superficial similarities.